Development of an immunochromatographic assay as a screen for detection of total phthalate acid esters in cooking oil. Issue 4 (16th February 2018) - He, Fan; Tian, Yuanxin; Xu, Zhenlin; Luo, Lin; Yang, Jinyi; Wang, Hong; Sun, Yuanming; Du, Qingfeng; Shen, Yudong
ABSTRACT: Phthalate acid esters (PAEs) contamination raised concerns as a result of migration from food packaging and environmental exposure. Because of the adverse effects of PAE reported in humans, the aim of this study was to examine the ability to screen for the detection these chemicals as an indicator of potential exposure. Too develop a sensitive screening test to determine PAE, a specific polyclonal antibody against phthalic acid (PA), the hydrolysate of PAEs, was used as a marker of total PAEs. This method involved the use of 4-aminophthalic acid (APA) as an immunizing hapten to generate antibody. Subsequently, this antibody conjugated with labeled gold nanoparticles (GNPs) was then used to develop an immunochromatographic assay (ICA) for visually detecting PA. After establishing optimal assay conditions, the ICA strip detected visually PA at 3 μg/ml rapidly in less than 5 min. Further, this assay exhibited reliable specificity for PA with no apparent cross-reactivity with structurally related PAEs. A significant correlation between data obtained with the ICA strip and high-performance liquid chromatography (HPLC) analysis was achieved using cooking oils as model spiked samples. The proposed use of ICA offers an effective tool for rapid on-site screening for total PAEs in cooking oils.